Biogenic Volatile Organic Compound and Respiratory CO2 Emissions after 13C-Labeling: Online Tracing of C Translocation Dynamics in Poplar Plants - Ghirardo, Andrea; Gutknecht, Jessica; Zimmer, Ina; Brüggemann, Nicolas; Schnitzler, Jörg-Peter (PLOS ONE, 2011)
Background Globally plants are the primary sink of atmospheric CO2, but are also the major contributor of a large spectrum of atmospheric reactive hydrocarbons such as terpenes (e.g. isoprene) and other biogenic volatile organic compounds (BVOC). The prediction of plant carbon (C) uptake and atmospheric oxidation capacity are crucial to define the trajectory and consequences of global environmental changes. To achieve this, the biosynthesis of BVOC and the dynamics of C allocation and translocation in both plants and ecosystems are important. Methodology We combined tunable diode laser absorption spectrometry (TDLAS) and proton transfer reaction mass spectrometry (PTR-MS) for studying isoprene biosynthesis and following C fluxes within grey poplar (Populus x canescens) saplings. This was achieved by feeding either 13CO2 to leaves or 13C-glucose to shoots via xylem uptake. The translocation of 13CO2 from the source to other plant parts could be traced by 13C-labeled isoprene and respiratory 13CO2 emission. Principal Finding In intact plants, assimilated 13CO2 was rapidly translocated via the phloem to the roots within 1 hour, with an average phloem transport velocity of 20.3±2.5 cm h−1. 13C label was stored in the roots and partially reallocated to the plants' apical part one day after labeling, particularly in the absence of photosynthesis. The daily C loss as BVOC ranged between 1.6% in mature leaves and 7.0% in young leaves. Non-isoprene BVOC accounted under light conditions for half of the BVOC C loss in young leaves and one-third in mature leaves. The C loss as isoprene originated mainly (76–78%) from recently fixed CO2, to a minor extent from xylem-transported sugars (7–11%) and from photosynthetic intermediates with slower turnover rates (8–11%). Conclusion We quantified the plants' C loss as respiratory CO2 and BVOC emissions, allowing in tandem with metabolic analysis to deepen our understanding of ecosystem C flux.